Formation of Disaster Resilient Villages (Destana) for Improvement Community Resilience to Disaster in Timpik Village, Semarang Regency - Zakiyah, Ismi; Susanti, Wahyu; Adinda, Marsaa Alyaa Aufaa; Pamungkas, Restu Adhi; Wahzudik, Niam (Jurnal Abdimas, 2025)
This community service activity aims to strengthen the capacity of rural communities in disaster preparedness through the establishment of a Disaster Resilient Village (Destana) in Timpik Village, Semarang Regency. The program was implemented using a participatory and collaborative approach based on BNPB Regulation No. 1 of 2012, involving village officials, the Regional Disaster Management Agency (BPBD), community leaders, and vulnerable groups. The implementation stages consisted of the Village Resilience Assessment (PKD), disaster risk assessment, development of disaster mitigation and preparedness plans, establishment of the Village Disaster Risk Reduction Forum (PRB), and the formation of a Community Disaster Volunteer Team. The results show an improvement in the Village Resilience Index from 36.27 (pratama level) to 51.73 (moderately resilient). The village's main strength lies in basic services and the existence of disaster management policies, while weaknesses remain in transportation, services for vulnerable groups, early warning systems, and post-disaster recovery mechanisms. Overall, the establishment of Destana in Timpik Village has successfully enhanced community preparedness and institutional resilience, although continuous capacity building, regular training, and the development of formal disaster management documents are still required.